TECHNICAL SKILL NEEDS OF TECHNICAL TEACHERS IN SOUTHSOUTH OF NIGERIA - Adavbiele, Justina A (European Scientific Journal, ESJ, 2013)
The existence of skill gap in technical teachers, particularly those in building technology is currently having a wide spread negative impact on both the teachers and craftsmen in terms of functions and productivity in work place. Lack of attention to tackle the gap will make the young recruits less attractive to employers, resulting in higher unemployment and greater difficulty in improving production to enhance the economy of the country. This study was designed to identify the skill gaps between technical skill needs and technical skill possessed by technical teachers in building technology in South-South Nigeria. Descriptive survey design was used. Two research questions and two hypotheses were raised. The data were analyzed using relevant statistical tools, which include frequency, means, correlation, standard deviation and ANOVA. The study revealed not only that there are skill shortages, but the level of shortages. Solutions proffered include provision of in-service training and the need for the government to provide facilities, machinery, tools and consumables among others in the various technical colleges needed by building technology teachers to build their skills as well as fulfilling the aim of technical education which is producing individuals that are selfreliant.